Role of cytochrome P450 monooxygenase in the bioactivation of aflatoxin B1 - Sureeporn Nualkaew,; Hirun Saelim,; Danai Tiwawech,; Tanate Panrat Imran Parvez,; Amornrat Phongdara, (Penerbit Universiti Kebangsaan Malaysia, 2017)
In a previous study, the gene EgP450 that encodes the proteins of 505 amino acids was isolated from oil palm. The recombinant protein EgP450 is bound to phenylurea-like herbicides which detoxify the substance. Aflatoxin B1 (AFB1), a mycotoxin produced by Aspergillus sp., is another toxic compound that is known to cause acute toxic effects and act as a hepatocarcinogenic agent. This study aimed to examine the role of EgP450 enzyme in mycotoxin bioactivation in human mesenchymal stem cells (hMSCs). Docking analysis showed that EgP450 is bound to the group of carcinogens, which includes AFB1, n-(2-fluorenyl) acetamide, n-n-butyl-n-butan-4-ol-nitrosamine, n-nitrosodiethylamine, n-nitrosodiethylamine and n-nitrosodimethylamine. An in vivo aflatoxin toxicity test on hMSCs and AFB1 induces the expression of Bmi-1 which is one of the markers for the development of cancer. The presence of EgP450 at 0.15 μg/mL could reduced the Bmi-1 expression in AFB1 induced cells. Moreover, this protein also showed some antioxidant activity. These results exhibited the enormous potential of EgP450 in the detoxification processes.